AB0679 The clinical value of nailfold capillaroscopy in the early diagnosis of systemic sclerosis. (15th June 2017) - Gao, W; Zhang, G; Zhang, L; Xu, K; Li, B; Yang, Y; Yan, M
Abstract : Background: Vascular changes was early pathological changes of SSc, gradually appearing with irreversible fibrosis of the skin and internal organs. Early diagnosis and assessment of the development and efficacy timely, could improve survival in patients with SSc. Objectives: To assess the value of nailfold capillaroscopy in the early diagnosis of systemic sclerosis (SSc). Methods: 60 patients with SSc and 55 patients with other connective tissue diseases.Data were extracted on clinical and laboratory parameters.2013 ACR/EULAR classification criteria and 1980 ACR criteria for SSc were evaluated. Results: The sensitivity of the 2013 criteria was 91.7% compared to 56.7% for the 1980 criteria ( P <0.001). The specifiity of two criteria was no significant difference. This sensitivity of the 2013 criteria was higher compared to the 1980 criteria among those with lcSSc (95.5% versus 50%).The pattern was consistent among those with disease duration <3 years (90.5% versus 57.1%, P <0.05), and disease duration ≥3 years (92.3% versus 56.4%, P <0.05). The sensitivity and specificity of nailfold capillaroscopy to determine SSc were 86.7% and 43.6%. Patients not fulfilling the two classification criteria were met the very early diagnosis of systemic sclerosishe, and often suffering from RP, and had an SSc pattern on nailfold capillaroscopy. Conclusions: The sensitivity of 2013 ACR/ EULAR classification criteria was higher compared with 1980 ACR classification criteria.The specificity of two classification criteria was no significant difference. This sensitivity of two criteria was higher among those with lcSSc and short disease duration.Scleroderma pattern were significantly associated with the development of systemic sclerosis. References: van den Hoogen F, Khanna D, Fransen J, et al.2013 classification criteria for systemic sclerosis: an American college of rheumatology/European league against rheumatism collaborative initiative[J]. Ann Rheum Dis, 2013, 72(11):1747–1755. Alhajeri H, Hudson M, Fritzler M, et al. The 2013 ACR/EULAR Classification Criteria for Systemic Sclerosis Out-perform the 1980 Criteria: Data from the Canadian Scleroderma Research Group[J]. Arthritis Care &Research, 2015, 67(4):582–587. Maricq HR. Wide-field capillary microscopy[J]. Arthritis Rheum, 1981, 24(9):1159–1165. Pavlov-Dolijanovic S, Damjanov NS, Stojanovic RM, et al.Scleroderma pattern of nailfold capillary changes as predictive value for the development of a connective tissue disease:a follow-up study of 3, 029 patients with primary Raynaud's phenomenon[J]. Rheumatol Int, 2012, 32(10):3039–3045. Marino Claverie L, Knobel E, Takashima L, et al.Organ involvement in Argentinian systemic sclerosis patients with "late" pattern as compared to patients with "early/active" pattern by nailfold capillaroscopy[J]. Clin Rheumatol, 2013, 32(6):839–843. Cutolo M, Grassi W, Matucci Cerinic M. Raynaud's phenomenon and the role of capillaroscopy[J]. Arthritis Rheum, 2003, 48(11):3023–3030. Disclosure of Interest: None declared